Gender Analysis of Tax Ethics Awareness Trust and Literacy in Decision Making - Adolf Z.D. Siahay; Entis Sutisna (Inovasi Analisis Data, 2025)
Purpose – To investigate the effects of tax conscience, tax attitude, tax administration satisfaction and tax literacy on tax decision and the role of gender as a moderator variable. This study addresses the dearth of knowledge on behavioral and demographic factors that are involved in building voluntary tax compliance. Design/methodology/approach – A quantitative approach with survey data was used, from 140 respondents in the mining sector in Indonesia. Direct effects were assessed with multiple linear regression analyses and gender moderation was assessed with use of interaction terms. Findings – Tax morale, tax awareness, tax administration satisfaction and tax literacy impact tax-related decision-making positively and significantly. Moreover, gender is shown to be a significant moderator of these relationships, which implies that male and female respondents may be processing tax-related stimuli quite differently with regard to compliance behavior. Originality/value – This is the first study to provide such an integrated model that incorporates a combination of behavioral, administrative and literacy variables and to jointly consider the moderating influence of gender in tax compliance research. Research Implications – Findings suggest the importance of fiscal education that responds closely to gender-specific differences and also that administrative strategies should be made more inclusive to achieve greater voluntary compliance. Specific types of nudges tailored on behavioral insights are useful to increase trust on the tax system and increase participation, also at the level of policymakers and tax authorities.